National panorama about teaching perspectives for improving Science teaching in Basic Education (Research, Society and Development, 2021)
Faced with a fragile scenario, in which 'everyone' has an accurate hunch to solve teaching problems, disseminating the opinion of educators is essential. This study aims to investigate and analyze 64 teaching perspectives (45 women and 19 men), aged between 23 and 58 years, to improve the teaching of Science in Basic Education in Brazil. With an investigative and qualitative nature, this study took place through the elaboration, application and analysis of a semi-structured questionnaire for teachers who are acting in the course of the Natural Sciences discipline of the 9th grade of Basic Education schools in Brazil. The categories of analysis were established: (1) Initial and continuing teacher education; (2) School structure and resources; and (3) Curriculum. Professors from 14 Brazilian states participated in the research, totaling representatives from the five regions of the country, who have one or more degrees in Biological Sciences, Mathematics, Chemistry and Pedagogy. The professors suggested to reformulate the initial formation of the professor, implementing disciplines related to technologies; and addressed the need for continuing education related to experimental activities, both for awareness, development and implementation of these in laboratories. Furthermore, they describe concerns about the student's responsibility towards their learning and the lack of family support; in addition to the accommodation of some professionals in teaching practice. Finally, we conclude that the teacher is part of the process of building a more humane and just society. And for that, it should be more valued.